The use of low doses of acepromazine as an aid for lameness diagnosis in horses: An accelerometric evaluation - López-Sanromán, F. J.; Cisneros, Gómez D.; del Arco, Varela M.; Llorente, Santiag I.; González, Santos M. (Veterinary and Comparative Orthopaedics and Traumatology, 2015)
Objectives: The aim of the present study was to quantify by accelerometry the trotting pattern of adult horses sedated with two different doses of acepromazine, in order to assess the use of this drug in equine lameness evaluations.Methods: Seven mature horses were used and three treatments were administered to each horse: saline solution, acepromazine (0.01 mg/kg), and acepromazine (0.02 mg/ kg). The portable gait analyzer used consisted of three orthogonal accelerometers that measure accelerations along the dorso -ventral, longitudinal, and lateral axes. Baseline values were obtained and after treatment, accelerometric recordings were repeated every five minutes during the first 20 minutes after the injection and then every 10 minutes thereafter for two hours. Ground-tolip distance was also measured.Results: Administration of acepromazine decreased some of the variables investigated and differences between doses were observed. Speed, stride frequency, and stride length were significantly reduced following treatments. For coordination parameters, no significant differences among values were observed. Energetic variables suffered only weak reductions whereas ground-to-lip distance values were significantly decreased up to 120 minutes after treatment.Clinical significance: Acepromazine produces significant alterations in the gait pattern with differences between doses, but it does not affect coordination variables in normal unexcited horses, and at a dose of 0.01 mg/kg may be the tranquilizer of choice for evaluating lameness in this setting.
Keywords: Horse; lameness; acepromazine; accelerometry